Capture Sequencing Enables Sensitive Detection of Tick-Borne Agents in Human Blood - Sanchez-Vicente, Santiago; Jain, Komal; Tagliafierro, Teresa; Gokden, Alper; Kapoor, Vishal; Guo, Cheng; Horn, Elizabeth J.; Lipkin, W. Ian; Tokarz, Rafal (Frontiers in Microbiology, 2022)
Assay sensitivity can be a limiting factor in the use of PCR as a tool for the detection of tick-borne pathogens in blood. We evaluated the performance of TBDCapSeq, a capture sequencing assay targeting tick-borne agents, to test 158 whole blood specimens obtained from the Lyme Disease Biobank. These included samples from 98 individuals with signs and symptoms of acute Lyme disease, 25 healthy individuals residing in Lyme disease endemic areas, and 35 samples collected from patients admitted to the Massachusetts General Hospital or referred to the infectious disease clinic. Compared to PCR, TBDCapSeq had better sensitivity and could identify infections with a wider range of tick-borne agents. TBDCapSeq identified a higher rate of samples positive for B. burgdorferi (8 versus 1 by PCR) and Babesia microti (26 versus 15 by PCR). TBDCapSeq also identified previously unknown infections with Borrelia miyamotoi, Ehrlichia, and Rickettsia species. Overall, TBDCapSeq identified a pathogen in 43 samples versus 23 using PCR, with 4 co-infections detected versus 0 by PCR. We conclude that capture sequencing enables superior detection of tick-borne agents relative to PCR.